Modalities, Identity, Belief, and Moral Dilemmas: Themes from Barcan Marcus (De Gruyter, 2015)
Modal logic; quantification; rationality
English
Keywords: Modal logic; quantification; rationality; thema EDItEUR::Q Philosophy and Religion::QD Philosophy; thema EDItEUR::Q Philosophy and Religion::QD Philosophy::QDH Philosophical traditions and schools of thought::QDHR Western philosophy from c 1800; thema EDItEUR::Q Philosophy and Religion::QD Philosophy::QDT Topics in philosophy::QDTL Philosophy: logic; thema EDItEUR::Q Philosophy and Religion::QD Philosophy::QDT Topics in philosophy::QDTQ Ethics and moral philosophy